Micromilling vs hand drilling in stable isotope analyses of incremental carbonates: The potential for δ13C contamination by embedding resin. (23rd May 2022) - Branscombe, Tansy; Lee‐Thorp, Julia; Schulting, Rick; Leng, Melanie
Abstract : Rationale: Embedding resins are commonly used to facilitate high‐resolution sampling for stable isotope analysis but anomalous δ 13 C values have been observed in some cases. Here we compare the results of microsampling strategies for hand‐drilled versus resin‐embedded micromilled samples from the same marine shells to assess whether resin contamination is implicated in δ 13 C spikes. The comparison allows assessment of the relative benefits for spatial resolution, seasonal range for both δ 18 O and δ 13 C, and sample failure rates. Methods: Hand‐drilled samples were obtained from two bivalve shells ( Spisula sachalinensis ), corresponding to micromilled samples on the same shells where high δ 13 C spikes were observed. All carbonate powders were analysed using a dual‐inlet Isoprime mass spectrometer and Multiprep device. Results from both sample sets were compared statistically. Results: No anomalous high δ 13 C values and no failures due to insufficient gas were observed in the hand‐drilled samples in contrast to the embedded micromilled sequences. Spatial resolution was reduced (~2.5×) in the former compared with the latter, resulting in a small reduction in the total range observed in the micromilled δ 13 C and δ 18 O values. Reduced sampling resolution between the two datasets was only significant for δ 18 O. Conclusions: For S. sachalinensis (as with other similar bivalves), rapid growth mitigates the reduced sampling resolution of hand drilling and does not significantly impact observed isotopic range and seasonal patterning. Occurrence of anomalous δ 13 C values were eliminated and failure rates due to insufficient sample size greatly reduced in the hand‐drilled dataset. We can find no other explanation for the occurrence of δ 13 C spikes than contamination by the embedding agent. We conclude that the logistical and interpretational benefits of careful hand drilling may be preferable to resin embedding for micromilling in marine shells, corals or speleothems where growth rate is rapid and the highest resolution is not required.